Peran Khutbah Jum'at dalam Menciptakan Kerukunan Antar Umat Beragama dalam Kehidupan Bermasyarakat - Siti Sofiyah (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
Harmony between religious communities in Indonesia, especially in our society, will be formed if people are aware that differences in beliefs and beliefs cannot be used as an excuse to hate each other and justify excessive fanaticism. The existence of religious plurality in society is a sunnatullah that must be an introduction to mutual understanding and mutual respect between people. This research is a qualitative research, with a study approach. The results of this study include; (1) Education Factor, Many people and residents of Gunung Anyar have received a good education, so they understand the concept of pluralism and tolerance between religions. (2) The social conditions of the residents of Gunung Anyar Rungkut Subdistrict, Surabaya, which are safe and far from the effects of thoughts of secularism, extremism, as well as information on sara issues, allow them to live in peace even though they have different religions and beliefs.